An anticipatory vision for the future schools in the Sultanate of Oman and the required skills for their leaders in the light of the Singaporean and Malaysian models - Al-Hinai, Moosa Ali Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to address the nature, characteristics, and objectives of future schools and introduce them and the most prominent specifications that must be met by their leaders in the light of foreign models, by relying on the descriptive analytical approach, The search tool was the documentary survey of published publications; Paper and electronic in Arabic and English, the study consisted of an introduction, three sections and a conclusion; Where the first topic dealt with: the nature of the future school and its features: it includes (its definition, philosophy, and features); The second dealt with: the foundations, intellectual premises, and justifications for development: It included: (The principles of the School of the Future include: the humanitarian principle, the developmental principle, the principle of education for science, the principle of education for work, the principle of education for life, the principle of integrated education, the principle of originality and innovation, and the components of institutional building It includes: school administration, curricula, teaching strategies, and the teacher; its characteristics and objectives); The third was devoted to the Singaporean and Malaysian models, and ended with the conclusion, which included the most important results, the study concluded: The leadership of the future school should have comprehensive objectives, including all components of the educational system. The leader must supervise the school activity, work to improve it, organize, manage and coordinate school work, It strives to improve the professional growth of teachers, and guides students, and the study recommends several recommendations, including: Preparing programs, training courses and workshops for future school leaders to develop their competence in relation to the study axes, as well as for the Ministry of Education to have A clear vision at raising the competencies and skills of future school leaders and training them according to the latest global developments in various fields, and provide the necessary capabilities for the School of the Future until Its leaders are able to use an effective system of incentives and rewards according to the teacher's achievement and creativity.
Keywords: Forward-Looking Vision; Future Schools; Educational Leadership; Singaporean and Malaysian Models; Sultanate of Oman